El infructuoso límite de publicaciones de prensa en España y en el Mercado Europeo Digital - Cabrera Minaya, Susana (2017)
This article analyzes the regulation of the limitation of contents aggregation in the Spanish Copyright Law. We describe its regulation, requirements and effectiveness. Furthermore it describes how unsuccessful it was for different European countries to legislate the protection of press contents in the digital field and the Proposal presented by the European Commission. Finally it describes the regulation of the limitation of current information in the Peruvian Copyright Law and the possible reasons that still motivate the absence of news aggregation in Latin America laws.